The role of nutrition in the management of health and diseases - Divya Sharma; Supriya Sharma
Dietary interventions exhibit promising efficacy in managing diverse chronic conditions and diseases. However, strong evidence and a structured framework are crucial before incorporating dietary interventions into health systems for their best effectiveness and success. This comprehensive review examines the health benefits of incorporating fruits, vegetables, nuts, herbs, and spices into dietary intake. These natural foods are abundant sources of essential vitamins, minerals, antioxidants, and anti-inflammatory compounds, offering a holistic approach to improving overall health and combating multiple diseases. The phytochemicals present in fruits and vegetables play a crucial role in promoting health by exerting antioxidant, anticancer, cardioprotective, immunomodulatory, anti-inflammatory, and effects within the human body. Particular attention has been paid to spices commonly found in Indian kitchens, such as turmeric, ginger, garlic, cinnamon, pepper, and cloves, which have been shown to possess significant therapeutic properties for managing various ailments. Regularly consuming these plant-based foods provides a natural and effective means of obtaining these health-promoting phytochemicals. In conclusion, this review underscores the importance of embracing a plant-rich diet to harness the numerous health benefits of fruits, vegetables, nuts, herbs, and spices. Overall, the findings describe the critical role of dietary choices in disease prevention and management, highlighting the potential of food in promoting long-term health and well-being.